FAKTOR YANG BERHUBUNGAN DENGAN KEGAGALAN DALAM PEMBERIAN ASI EKSKLUSIF PADA BAYI UMUR 0-6 BULAN DI KLINIK PRATAMA DANDY - Debby Pratiwi (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
Background: The high rate of exclusive breastfeeding failure was 66.7%. Breast milk is the first, the main and best food for babies, which is natural. Exclusive breastfeeding is breastfeeding without additional food and drinks for infants aged 0-6 months, even plain water is not given in this stage of exclusive breastfeeding. Objective: The purpose of this study was to determine the relationship between knowledge, work and family support with the failure to provide exclusive breastfeeding to infants aged 0-6 months in Klinik Pratama Dandy in 2021. Methods: This study used an analytic survey design with a cross-sectional approach. The population were all breastfeeding mothers who had babies aged >6 months totalling 30 respondents and all were taken as the sample. The analysis in this study used univariate and bivariate analyses with the Chi-Square test. Result: The results of this study with the Chi-Square test on the knowledge of mothers with failures in exclusive breastfeeding obtained p-value=0.000, jobs with failure to provide exclusive breastfeeding obtained p-value=.049, and family support with failure to provide exclusive breastfeeding obtained p-value=.001. Conclusion: The conclusion is that there is a relationship between knowledge, work and family support with the failure to provide exclusive breastfeeding for infants aged 0-6 months in Klinik Pratama Dandi in 2021. It is recommended that health workers improve health promotion about the importance of exclusive breastfeeding. to infants aged 0-6 months.